Correlation between Epstein–Barr virus and anti-cytomegalovirus/-herpes simplex virus/-Toxoplasma gondii antibodies in Chongqing, China: a cross-sectional observational study - Zhang, Youyu; Song, Shupeng; Wu, Yilin; Ding, Beining; Chen, Xuenuo; Li, Qian; Du, Yuxia; Liu, Huiling; Li, Yongguo (Frontiers in Medicine, 2025)
BackgroundEpstein–Barr virus (EBV) infects more than 95% of the global population, and EBV reactivation is associated with the development of various diseases. The aims of this study were (1) to investigate the epidemiology of EBV, CMV, HSV, and Toxoplasma gondii infections and their associations with serum antibody profiles and (2) to explore the relationships between EBV infection and reactivation and the antibody status of Toxoplasma gondii, CMV, and HSV.MethodsThis retrospective study detected EBV-specific antibody profiles or plasma EBV-DNA, as well as antibodies against Toxoplasma gondii, cytomegalovirus (CMV), and herpes simplex virus (HSV). Basic demographic information, including age and sex, was collected to assess the EBV infection status and the prevalence of antibodies against Toxoplasma gondii, CMV, and HSV in different populations.ResultsA total of 3,046 hospitalized patients (1,524 male, 1,522 female) who underwent antibody testing for Toxoplasma gondii, CMV, and HSV were included in the study. The overall serum positivity rates for Toxoplasma gondii IgG, CMV IgG, and HSV IgG increased with age, with overall rates of 16.84, 97.50, and 91.20%, respectively. Among the 1,079 patients who underwent EBV-DNA testing, the lowest virus detection rate (9.97%) was found in the 21–40-year-old age group, with a progressively increasing rate with age. Additionally, compared with patients who were negative for Toxoplasma gondii IgG, those with Toxoplasma gondii IgG positivity had significantly higher rates of EBV-EA-IgG and EBV-VCA-IgA antibody positivity (p = 0.032; p < 0.001). Furthermore, patients with EBV reactivation had the highest CMV IgM antibody positivity rate (60.53%), followed by those with primary EBV infection (45.45%), whereas patients without EBV infection had the lowest rate (25.75%), with statistically significant differences between the groups.ConclusionEBV antibody profiles positivity rates were higher in patients with Toxoplasma gondii IgG positivity than in those with Toxoplasma gondii IgG negativity. The CMV IgM antibody positivity rate was significantly higher in EBV reactivation group than in other groups. These results highlight potential diagnostic relevance of co-testing for EBV and CMV in suspected reactivation cases.